Advances in the research of the role of macrophage/microglia polarization-mediated inflammatory response in spinal cord injury - Fu, Sheng-Ping; Chen, Si-Yu; Pang, Qi-Ming; Zhang, Meng; Wu, Xiang-Chong; Wan, Xue; Wan, Wei-Hong; Ao, Jun; Zhang, Tao (Frontiers in Immunology, 2022)
It is often difficult to regain neurological function following spinal cord injury (SCI). Neuroinflammation is thought to be responsible for this failure. Regulating the inflammatory response post-SCI may contribute to the recovery of neurological function. Over the past few decades, studies have found that macrophages are one of the primary effector cells in the inflammatory response following SCI. Growing evidence has documented that macrophage are plastic cells that can polarize in response to microenvironmental signals into M1 and M2 macrophages. M1 macrophages produce pro-inflammatory cytokines to induce inflammation and worsen tissue damage, while M2 macrophages have anti-inflammatory activities in wound healing and tissue regeneration. Recent studies have indicated that the transition from the M1 to the M2 phenotype of macrophages supports the regression of inflammation and tissue repair. Here, we will review the role of the inflammatory response and macrophages in SCI and repair. In addition, we will discuss potential molecular mechanisms that induce macrophage polarization, with emphasis on neuroprotective therapies that modulate macrophage polarization, which will provide new insights into therapeutic strategies for SCI.